A method for identifying the origin of pyroasphalt optical structure based on quantitative nanomechanics
The height and modulus map of coke asphalt were obtained through atomic force microscope scanning, quantitatively identify its optical structural units, and solve the problem that it is difficult to understand the causes of the optical structure of coke asphalt in the prior art, and realize the detailed arrangement and mechanical properties of its microcrystals. Analysis provides a basis for reflectivity selection and maturity evaluation.
Patent Information
- Application Number
- CN202210807728.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-10
- Filing Date
- 2022-07-11
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2042-07-11
AI Technical Summary
The existing technology is difficult to quantitatively determine the uniform slight mosaic, concave spherical and convex spherical optical structural units of coking asphalt. There is a lack of research on the causes of the optical structure of focusing asphalt, which affects its microcrystal arrangement, deformation and mechanical properties. It is difficult to accurately select reflectivity values and perform maturity evaluation.
Scan the coke asphalt sample by atomic force microscope to obtain the height map and modulus map of its anisotropic optical structure, and determine different optical structural units according to the specific height value and modulus value range, including uniform slight mosaic type and depression Small spherical and convex small spherical units, combined with a smooth and flattened substrate of three-dimensional height map and modulus map, were quantitatively characterized.
Quantitative characterization of the causes of the optical structure of focus asphalt is realized, helping to understand its microcrystalline arrangement method and mechanical properties heterogeneity, providing an important reference for the selection of reflectivity values and maturity evaluation, and improving the maturity evaluation of focus asphalt and Understanding of mechanical properties.
Smart Images

Figure CN115015582B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for studying the optical structure of pyroasphalt, and in particular to a method for identifying the formation cause of the optical structure of pyroasphalt based on quantitative nanomechanics. Background Art
[0002] Asphalt is a dark brown complex mixture composed of hydrocarbons of different molecular weights and their non-metallic derivatives. It is a kind of high-viscosity organic liquid. It is in liquid state, with a black surface and is soluble in carbon disulfide. Asphalt is an organic gelling material that is waterproof, moisture-proof and anti-corrosive. Asphalt can be mainly divided into three types: coal tar asphalt, petroleum asphalt and natural asphalt: among them, coal tar asphalt is a by-product of coking. Petroleum asphalt is the residue after crude oil distillation. Natural asphalt is stored underground, some of which form mineral layers or accumulate on the surface of the earth's crust. Asphalt is mainly used in industries such as coatings, plastics, rubber, and paving roads. When natural asphalt is subjected to high temperature or deep burial, it will form tar asphalt with a strong anisotropic optical structure.
[0003] At present, there is a lack of research on the causes of the optical structure of pyroasphalt, especially for the three main optical structure units of pyroasphalt: uniform slightly mosaic type, concave spherical unit and convex spherical unit. These three types of units are difficult to quantitatively identify.
[0004] Therefore, a quantitative method is needed to identify the origin of the optical structure of pyroasphalt, which will help to better understand the heterogeneity of the crystallite arrangement, deformation and mechanical properties of pyroasphalt, and provide an important reference for accurately selecting reflectance values and conducting maturity evaluation. Summary of the invention
[0005] The present invention provides a method for identifying the origin of the optical structure of pyroasphalt based on quantitative nanomechanics, and proposes a method for quickly characterizing the anisotropic optical structure of pyroasphalt according to height values and modulus values.
[0006] The present invention provides a method for identifying the cause of formation of pyroasphalt optical structure based on quantitative nanomechanics, comprising:
[0007] S1. Prepare pyroasphalt samples;
[0008] S2. Scanning the pyrolysis pitch sample with an atomic force microscope to obtain a height map and a modulus map of the anisotropic optical structure, wherein the anisotropic optical structure includes a uniform slightly mosaic type, a concave spherical unit, and a convex spherical unit;
[0009] S3. Identify the cause of the anisotropic optical structure of pyroasphalt through height map and modulus map;
[0010] In the height map and modulus map,
[0011] Taking the uniform slightly mosaic type as the reference plane with a height of 0, and the modulus value of 9.8±0.5GPa, it is identified as a uniform slightly mosaic type, in which the arrangement of microcrystals has no obvious direction, and the interatomic force and the intermolecular force coexist in the vertical direction;
[0012] The height value is -10 to -45 nm, and the modulus value is 4.8 ± 0.5 GPa, which is identified as a concave spherical unit. Its microcrystals are arranged in a nearly horizontal direction, and the corresponding intermolecular forces are weak.
[0013] The height value is 10 to 45 nm, and the modulus value is 14.3±0.5 GPa, which is identified as a raised spherical unit; its microcrystals are arranged in a nearly vertical direction, corresponding to strong interatomic forces.
[0014] As an optimization, pyroasphalt samples were prepared, including
[0015] Making thin sections of dolomite with anisotropic pyroasphalt;
[0016] polishing the slice to obtain a polished light slice;
[0017] Cut the optical slices into specimens with a diameter less than 15 mm.
[0018] As an optimization, the sample is scanned with an atomic force microscope. The specific operations include:
[0019] Select needle;
[0020] Bending sensitivity DS calibration: at different scanning positions, collect at least three force curves of the standard sample, calculate the slope of the force curve, and take the average of the three measured slopes;
[0021] Set the elastic coefficient k and the curvature radius r;
[0022] scanning.
[0023] As an optimization, the height map and modulus map are converted into a three-dimensional height map and a three-dimensional modulus map, and the three-dimensional height map and the three-dimensional modulus map are smoothed and the base is flattened.
[0024] Compared with the prior art, the present invention has the following beneficial effects: through the three-dimensional quantitative characterization of the anisotropic optical structure of pyroasphalt, it is helpful to understand the arrangement mode of pyroasphalt microcrystals, deformation and mechanical property heterogeneity, and provide a reference for accurately selecting reflectivity values and conducting maturity evaluation. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of this application. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0026] Figure 1 is a flow chart of an embodiment of the present invention;
[0027] Figure 2 This is a corresponding diagram between the optical structure of the present invention and the surface concavo-convex;
[0028] Figure 3 A three-dimensional height map and a three-dimensional modulus map of the anisotropic optical structure of the present invention;
[0029] Figure 4 This is the random reflectivity frequency distribution and cause identification model of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0031] As attached Figure 1 FIG. 1 is a flow chart of a method for identifying the cause of formation of pyroasphalt optical structure based on quantitative nanomechanics according to the present invention, the method comprising:
[0032] Step 1: Prepare the pyroasphalt sample; specifically including:
[0033] Making anisotropic pyroasphalt dolomite thin sections;
[0034] Step 2: polish the slice to obtain a polished light slice; the light slice polishing process uses 400 mesh, 1200 mesh, and 2500 mesh sandpaper for 5 minutes each, with a force of 25N; then polish with Buehler polycrystalline diamond particles for 15 minutes, with a force of 20N. Fine polishing uses 0.05um and 0.02um alumina polishing suspension for 3 minutes each, with a force of 20N. Finally, water polishing for 1 minute, with a force of 20N, to ensure that the pyroasphalt surface is clean and has no obvious scratches under a 1000x microscope.
[0035] Step 3: Cut the polished slice into samples with a diameter less than 15 mm.
[0036] Step 4: Needle selection and instrument settings; Select the RTESPA-525A (TAP-525A) probe and place the No. 5 standard SAPPHIRE-12M sapphire on the scanning stage of the Bruker Multimode 8 atomic force microscope. Adjust the laser optical path to maximize the SUM value, and adjust the quadrant knob to make the quadrant values Hor and Ver as close to zero as possible. Open the instrument's built-in software Nanoscope 9.1 and select PeakForce QNM in Air mode for imaging. Set the needle insertion according to Microscope>Engage Settings, and ensure that the Amplitude and Setpoint values are close to 150nm and 0.15V respectively to protect the probe tip. Select a smaller Scan Size and Scan Rate, manually control the scanning parameters, set the PeakForce Setpoint value so that it does not exceed 0.1V, and click Engage to start needle insertion. Scan several pictures of different scales to ensure that the sapphire surface in the field of view is clean and there are no obvious contaminants, and then proceed to the next step of calibration.
[0037] Bending sensitivity calibration; click the Ramp button, set the Ramp parameters, set the Ramp size to 30 or 20nm, set the TrigThreshold value to 0.05V, set the data channel to Deflection Error vs.Z, click Start Single Ramp at least three times at different scanning positions, and collect at least three force curves of the standard sample; pull the dotted line to select the range, select the nearly horizontal part, and perform the base leveling operation Baseline Correction, Execute; click Multiple Ramp Plot to pull the dotted line to select the part where the needle tip contacts the sample, click the menu Commands, Update sensitivity to obtain the slope, read the Deflection Sensitivity value, and perform the same operation on the other two force curves to obtain the Deflection Sensitivity value. Finally, average the three measured Deflection Sensitivity values. Return to the Nanoscope software and fill the average Deflection Sensitivity value into Calibrate>Detector>DeflectionSensitivity. Note that the unit nm / V must be included. Reduce the amplitude, set the PeakForce Amptitude to 15nm, the PeakForce Setpoint to 0.05V, and click Update Sens to perform DDS3 calibration.
[0038] Replace the graphite standard sample HOPG-12M (nominal modulus is 18GPa) that comes with the instrument, set the elastic coefficient k, and the k value should be as close as possible to the nominal value of the probe RTESPA-525A (TAP-525A) of 200N / m; apply force (about 0.1V) to make the indentation depth reach 2nm, increase the amplitude Amptitude to around 20nm, and ensure that the indentation depth will increase after slight force application. Using the principle E∝k / √R and the formula R correction value = R current value × (E measured value / E nominal value)2, adjust and correct the curvature radius so that the modulus graph display value is 18GPa. At this time, the curvature radius r is obtained. The significance of setting k and r is to make the probe indent into the sample to a depth close to that of the graphite standard sample, and at this time, the accurate modulus result can be obtained by scanning.
[0039] Step 5: Scanning. The sample is scanned with an atomic force microscope, the atomic force microscope model is a German Bruker MultiMode 8 atomic force microscope, the mode is PeakForce QNM in Air mode, and the modulus map of the anisotropic optical structure is obtained (such as Figure 2 and Figure 3 ), this anisotropic optical structure is specifically composed of uniform slightly mosaic-type and spherical units. The modulus diagram reveals the three-dimensional morphology and mechanical properties of the pyroasphalt surface. It can be seen that the surface of the spherical unit is concave and convex, where the concave corresponds to the bright area under the microscope and has a lower modulus value; the convex corresponds to the dark area under the microscope and has a higher modulus. The uniform slightly mosaic-type unit has no obvious concave and convex undulations and has a modulus between the first two. The cause of the optical structure of pyroasphalt is revealed.
[0040] In order to facilitate understanding and observation, the modulus map and height map were converted into three-dimensional modulus map and three-dimensional height map using NanoScope Analysis 1.8 software. The three-dimensional modulus map and three-dimensional height map were smoothed and the base was flattened to obtain the processed three-dimensional height map, which facilitated the understanding of the data.
[0041] NanoScope Analysis 1.8 software was used to perform statistical calculations of the modulus, which facilitated the revelation of the causes of the optical structure of pyroasphalt, the frequency distribution of random reflectivity, and the cause model (e.g. Figure 4 shown).
[0042] The direct optical cause of anisotropic pyroasphalt is the difference in surface nanoscale micro-deformation caused by viscosity differences.
[0043] The uniform, slightly mosaic structure is composed of smaller crystallites, has a higher viscosity, and only slightly deforms.
[0044] The spherical unit structure is composed of larger crystallites, has a lower viscosity, is easily deformed, and forms a concave-convex surface.
[0045] This deformation produces a concave and convex surface that can enhance or reduce the reflection of light, resulting in a bright and dark optical structure, which directly leads to a double-peak distribution of random reflectivity. That is, the concave and convex arc surface can converge and diverge the reflected light, thus forming an anisotropic optical structure with distinct light and dark, which further affects the value of reflectivity.
[0046] Relatively speaking, the raised area has a slight effect on the reflectivity, while the recessed area has a greater effect on the reflectivity, causing an abnormal increase in the reflectivity.
[0047] The concave and convex surface of the ball reflects that the graphite crystallites in the pyroasphalt are deformed in three-dimensional space and the crystallites are arranged in different directions. That is, the curved crystal stacking structure inside the ball is gradually exposed during the polishing process, forming a concave and convex arc surface. Taking the uniform and slightly mosaic pyroasphalt as the 0 height reference plane, the height of the concave spherical unit is about -10 to -45nm, and the height of the convex spherical unit is about 10 to 45nm.
[0048] The nanomechanical properties of pyroasphalts with different optical structures are heterogeneous. The modulus of the convex spheres is relatively large, about 14.3±0.5GPa, which is judged to be caused by the arrangement of the microcrystals in a near vertical direction, and the corresponding interatomic forces are relatively strong; the modulus of the concave spheres is relatively small, about 4.8±0.5GPa, which is judged to be caused by the arrangement of the microcrystals in a near horizontal direction, and the corresponding intermolecular forces are relatively weak. The modulus of the uniform and slightly mosaic pyroasphalt is between the two, at 9.8±0.5GPa, which is judged to be caused by the arrangement of the microcrystals without obvious direction, and the vertical interatomic forces and intermolecular forces coexist.
[0049] The difference in modulus can also be used to identify the causes of other optical structures (such as streamline structures and fiber structures).
[0050] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, ordinary technicians in the field should understand that the specific implementation methods of the present invention can still be modified or some technical features can be replaced by equivalents without departing from the spirit of the technical solution of the present invention, which should be included in the scope of the technical solution for protection of the present invention.
Claims
1. A method for identifying the origin of the optical structure of pyroasphalt based on quantitative nanomechanics, characterized in that: include: S1. Preparation of pyroasphalt samples, including: Making thin sections of dolomite with anisotropic pyroasphalt; The thin slice is polished to obtain a polished thin slice, wherein the thin slice polishing specifically includes: Use 400-grit, 1200-grit, and 2500-grit sandpaper for 5 minutes each, with a force of 25 N; Then, polishing was performed with Buehler polycrystalline diamond particles for 15 min with a force of 20 N; Then use 0.05 um and 0.02 um alumina polishing suspension for 3 minutes each, with a force of 20 N; Finally, polish with water for 1 minute and apply a force of 20 N; Cut the optical slices into specimens with a diameter less than 15 mm; S2. Scanning the pyrolysis pitch sample with an atomic force microscope to obtain a height map and a modulus map of the anisotropic optical structure, wherein scanning the sample with an atomic force microscope specifically includes: Needle selection and instrument setup; For the bending sensitivity DS calibration, at least three force curves of the standard sample were collected at different scanning positions, and the slope of the force curve was calculated, and the average of the three measured slopes was taken; Set the elastic coefficient k and the curvature radius r; scanning; The anisotropic optical structure includes uniform slightly mosaic type, concave spherical type unit and convex spherical type unit; S3, converting the above-mentioned height map and modulus map into a three-dimensional height map and a three-dimensional modulus map, and smoothing and flattening the base of the three-dimensional height map and the three-dimensional modulus map to identify the cause of the anisotropic optical structure of the pyroasphalt; wherein in the three-dimensional height map and the three-dimensional modulus map, The uniform and slightly mosaic type is used as the reference surface of 0 height, and its modulus value is 9.8±0.5 GPa, which is identified as the uniform and slightly mosaic type; The height value is -10 to -45 nm, and the modulus value is 4.8±0.5 GPa, which is identified as a concave spherical unit, which appears bright under the reflection of light; The height value is 10 to 45 nm, and its modulus value is 14.3±0.5 GPa, which is identified as a raised spherical unit; it appears dark under reflection of light.
